TELISITAS VERBA MAJEMUK –KOMU (―込む) PADA BAHASA JEPANG - Najmudin, Onin; Rahmat, Nandang (Fakultas Komunikasi, Sastra, dan Bahasa, 2017)
A telic event refers to an event with an endpoint whereas an atelic event is one that has no endpoint from compound verb of V1+komu. This research aimed to identify telicity or the existence of endpoint of compound verb of V1+komu. Related to its telicity, compound verb of V1+komu consists of two; thematic compound verb and aspectual compound verb. Thematic V1+komu compound verb is one that its telicity is defined by komu verb that adds its objective meaning toward V1, giving telic meaning to V1+komu compound verb. On the other hand, aspectual V1+komu is an atelic compound verb as komu verb as V2  does not add any aspectual meaning